The book of life - Harkness, Deborah E., 1965- (New York, New York : Viking, 2014)
Historian witch Diana Bishop and vampire scientist Matthew Clairmont return to the present to face new crises and old enemies. But the real threat to their future has yet to be revealed.
Keywords: Witches -- Fiction; Women historians -- Fiction; Vampires -- Fiction; Science and magic -- Fiction; Time travel -- Fiction; Fantasy fiction; Love stories